Akselerasi Pelaksanaan Otonomi Daerah dalam Globalisasi Ekonomi - Ahmad Jamli (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1998)
The globalisation of economy, which will take place all over the world, is also coming to Indonesia. In turn, this phenomenon of globalisation may influence all aspects of Indonesian development. Various changes caused by globalisation as well as technological development have to be responded appropriately in the development strategy. The centralised development strategy and dominant role of government need to be revised toward decentralised strategy and participatory development by the private sector. It is therefore essential to explore other alternative strategies of implementation of local autonomy in order to respond globalisation properly. This essay discusses various impacts of globalisation and development strategy alternatives that could be adopted by the Indonesian Government to face the market liberalisation. By adopting local autonomy policy, it is hoped that Indonesia can obtain some benefit from globalisation.